WILLINGNESS TO PAY MASYARAKAT UNTUK MENGGUNAKAN PARKIR ELEKTRONIK DI KABUPATEN ACEH BESAR - Irham Syahputra; T. Zulham (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
Abstrack This study aims to determine what factors influence the willingness to pay the public to use parking electronic system in the Aceh Besar District. The data used are primary data obtained from the results of questionnaires distributed to residents in Aceh Besar District. The number of samples in this study were 50 respondents two-wheeled and 50 four-wheeled riders. The analytical model used in this study is a multiple linear regression model, based on the results of the study found that those that affect the willingness to pay the public to use parking electronic system are income and payment methods. The implication of this research is that it is worth noting to carry out the construction of parking lots with electronic systems whether the government or the private sector to provide security, convenience, and reduce negative impacts and theft in parking locations. At the 95 percent confidence level this study is statistically acceptable.Keywords: willingness to pay, income, education, electronic parking system, multiple linear regression